A Taxon-Specific and High-Throughput Method for Measuring Ligand Binding to Nicotinic Acetylcholine Receptors - Christina N. Zdenek; Richard J. Harris; Sanjaya Kuruppu; Nicholas J. Youngman; James S. Dobson; Jordan Debono; Muzaffar Khan; Ian Smith; Mike Yarski; David Harrich; Charlotte Sweeney; Nathan Dunstan; et al. (Toxins, 2019)
The binding of compounds to nicotinic acetylcholine receptors is of great interest in biomedical research. However, progress in this area is hampered by the lack of a high-throughput, cost-effective, and taxonomically flexible platform. Current methods are low-throughput, consume large quantities of sample, or are taxonomically limited in which targets can be tested. We describe a novel assay which utilizes a label-free bio-layer interferometry technology, in combination with adapted mimotope peptides, in order to measure ligand binding to the orthosteric site of nicotinic acetylcholine receptor alpha-subunits of diverse organisms. We validated the method by testing the evolutionary patterns of a generalist feeding species (Acanthophis antarcticus), a fish specialist species (Aipysurus laevis), and a snake specialist species (Ophiophagus hannah) for comparative binding to the orthosteric site of fish, amphibian, lizard, snake, bird, marsupial, and rodent alpha-1 nicotinic acetylcholine receptors. Binding patterns corresponded with diet, with the Acanthophis antarcticus not showing bias towards any particular lineage, while Aipysurus laevis showed selectivity for fish, and Ophiophagus hannah a selectivity for snake. To validate the biodiscovery potential of this method, we screened Acanthophis antarcticus and Tropidolaemus wagleri venom for binding to human alpha-1, alpha-2, alpha-3, alpha-4, alpha-5, alpha-6, alpha-7, alpha-9, and alpha-10. While A. antarcticus was broadly potent, T. wagleri showed very strong but selective binding, specifically to the alpha-1 target which would be evolutionarily selected for, as well as the alpha-5 target which is of major interest for drug design and development. Thus, we have shown that our novel method is broadly applicable for studies including evolutionary patterns of venom diversification, predicting potential neurotoxic effects in human envenomed patients, and searches for novel ligands of interest for laboratory tools and in drug design and development.